Metal-organic cage crosslinked nanocomposites with enhanced high-temperature capacitive energy storage performance - Shuo Zhao; Weifeng Peng; Le Zhou; Shuqi Dai; Weibin Ren; Erxiang Xu; Yao Xiao; Mufeng Zhang; Mingjun Huang; Yang Shen; Ce-Wen Nan (Nature Communications)
Abstract Polymer dielectric materials are widely used in electrical and electronic systems, and there have been increasing demands on their dielectric properties at high temperatures. Incorporating inorganic nanoparticles into polymers is an effective approach to improving their dielectric properties. However, the agglomeration of inorganic nanoparticles and the destabilization of the organic-inorganic interface at high temperatures have limited the development of nanocomposites toward large-scale industrial production. In this work, we synthesize metal-organic cage crosslinked nanocomposites by incorporating self-assembled metal-organic cages with amino reaction sites into the polyetherimide matrix. The in-situ crosslinking by self-assembled metal-organic cages not only achieves a homogeneous distribution of inorganic components, but also constructs robust organic-inorganic interfaces, which avoids the interfacial losses of conventional nanocomposites and improves the breakdown strength at elevated temperatures. Ultimately, the developed nanocomposites exhibit exceptionally high energy densities of 7.53 J cm−3 (150 °C) and 4.55 J cm−3 (200 °C) with charge-discharge efficiency of 90%.